EFL Students’ Perceptions of the Impact of ChatGPT Usage on Critical Thinking Skills - Allvian Ika Fiki Susanto; Aziza Restu Febrianto; Afi Normawati; Antonius Sugeng Setyawan Nur; Efrika Siboro (Surakarta English and Literature Journal, 2025)
This study aims to investigate the students’ perceptions on the usage of ChatGPT toward their critical thinking skills in the EFL classroom and the challenges faced by the students in using ChatGPT in the EFL classroom. The research is conducted in the form of a mixed-method research design. It uses questionnaires and interviews to collect the research data. The results of the study show that the students have positive perceptions on the usage of ChatGPT to enhance their critical thinking skill in the EFL classroom. The second finding is that there are two challenges faced by the students, the tool’s inaccurate feedback and also the student’s tendency to overreliance on the tool.